Supplementation with cyanidin and delphinidin mitigates high fat diet-induced endotoxemia and associated liver inflammation in mice. Issue 2 (4th January 2022) - Cremonini, Eleonora; Iglesias, Dario E.; Matsukuma, Karen E.; Hester, Shelly N.; Wood, Steven M.; Bartlett, Mark; Fraga, Cesar G.; Oteiza, Patricia I.
Abstract : Short-term supplementation of mice with cyanidin and delphinidin mitigates the metabolic endotoxemia and associated liver inflammation triggered by consumption of a high fat diet (HFD). Abstract : Consumption of high fat diets (HFD) and the associated metabolic endotoxemia can initiate liver inflammation and lipid deposition that with time can progress to non-alcoholic fatty liver disease (NAFLD). We previously observed that 14 weeks supplementation with the anthocyanidins cyanidin and delphinidin mitigated HFD-induced metabolic endotoxemia and liver insulin resistance, steatosis, inflammation and oxidative stress. This work investigated if a 4-week supplementation of mice with a cyanidin- and delphinidin-rich extract (CDRE) could mitigate or reverse HFD (60% calories from lard fat)-induced liver steatosis and inflammation. After a first 4-weeks period on the HFD, mice showed increased endotoxemia and activation of liver proinflammatory signaling cascades. Supplementation with CDRE between weeks 4 and 8 did not mitigate liver steatosis or the altered lipid and glucose plasma levels. However, CDRE supplementation reverted HFD-induced metabolic endotoxemia, in parallel with the mitigation of the overexpression of hepatic TLR2 and TLR4, and of the activation of: (i) NF-κB, (ii) AP-1 and upstream mitogen-activated kinases p38 and ERK1/2, and (iii) HIF-1. Thus, even a short-term consumption of cyanidin and delphinidin could help mitigate the adverse consequences, i.e. metabolic endotoxemia and associated liver inflammation, triggered by the regular consumption of diets rich in fat.